Un essai sur la personne en diachronie - Frleta, Tomislav (Vestnik za tuje jezike, 2014)
In the present article the author, seeks to show how the loss of the verbal inflection influences, from the diachronic point of view, the use of the possessive in contemporary French. Starting with Latin, in which the use of the possessive with concepts from the personal sphere was rather rare, even exceptional, the present article follows, through the different periods of the French language, the appearance of the possessives in constructions involving body parts, clothes and the family. It is shown that, in one specific moment in the history of the French, there was simultaneous use of the possessive and the article for the concepts in question. The author justifies that phenomenon as the consequence of the (partial) loss of the person from the French verbal system.
Keywords: francoščina; French; historična slovnica; glagolsko pregibanje; oseba; svojilni zaimek; člen